MANAGEMENT STRATEGIES FOR RESEARCH, INNOVATION, AND INVENTION TO ENHANCE STUDENT DEVELOPMENT AT TRANG TECHNICAL COLLEGE - Buain, Thepin; Weeraponkan, Boonlert; PhrakhruPrachotkitchaphon (Journal of Educational Review Faculty of Education in MCU, 2026)
This research article aims to: 1) study the management environment for research, development, innovation and invention; 2) create a management strategy framework for research, development, innovation and invention; and 3) present and evaluate the proposed management strategy for research, development, innovation and invention to develop students at Trang Technical College. This was a qualitative research with the research process as follows: the first step, an environmental analysis, involved collecting data through in-depth interviews with 15 key informants; the second step, the strategy creation, involved in-depth interviews with 10 experts; and the final step, the strategy presentation and evaluation, involved focus group discussions with 8 experts. Data were analyzed using content analysis. The research results found that: 1) The management environment for research, development, innovation and invention had strengths in the educational institution, namely structure and policy, possibly because the institution had a clearly structured research and innovation management system; and opportunities lie in technology, as the institution has adopted technology at all levels, including management, teaching, and communication, which was conducive to the development of students at Trang Technical College. 2) The management strategy for research, development, innovation and invention to develop students at Trang Technical College consists of philosophy, vision, mission, goals, and strategies. Each strategy had the following sub-components: (1) strategic goals, (2) success indicators, and (3) projects and activities. The strategy for managing research, development, innovation, and invention to develop students at Trang Technical College consists of 5 strategies: Strategy 1: Managing to accelerate the expansion of research, innovation, and invention; Strategy 2: Promoting and developing personnel skills to create inventions and innovations; Strategy 3: Promoting and enhancing the learning process through research and innovation; Strategy 4: Promoting resources and learning sources for creating inventions and innovations; and Strategy 5: Driving inventions and innovations towards practical application. 3) The results of the presentation and evaluation of the strategies for managing research, development, innovation, and invention to develop students at Trang Technical College showed that they were appropriate, feasible, and beneficial, and could be implemented.